AB0752 DRUG RETENTION AND REMISSION RATES IN 14, 261 BIOLOGIC-NAÏVE PATIENTS WITH PSORIATIC ARTHRITIS STARTING TNF INHIBITOR TREATMENT IN ROUTINE CARE – RESULTS FROM 12 REGISTRIES IN THE EUROSPA RESEARCH COLLABORATION. (June 2019) - Brahe, Cecilie Heegaard; Ørnbjerg, Lykke; Jacobsson, Lennart T.H.; Nissen, Michael; Kristianslund, Eirik; Mann, Heřman; Santos, Maria Jose; Pombo-Suarez, Manuel; Nordström, Dan; Rotar, Ziga; Gudbjornsson, Björn; Onen, Fatos; et al.
Abstract : Background: The efficacy of Tumour Necrosis Factor inhibitor (TNFi) in patients with psoriatic arthritis (PsA) has been investigated in randomized controlled trials (RCTs) with strict inclusion and exclusion criteria. Patients treated in routine care are more heterogeneous and only ≈20-30% of patients receiving TNFi in routine care would have been eligible to be enrolled in the RCTs 1 . This emphasizes the need for real-world observational data as a valuable supplement to RCTs. Studying large patient groups from several European countries would increase the external validity of the results. Objectives: To investigate Tumour Necrosis Factor inhibitor (TNFi) retention rates at 12 months (primary objective), 6 and 24 months, and remission rates at the same time-points in biologic-naïve patients with PsA from the EuroSpA Collaboration. Methods: Prospectively collected data on PsA patients from 12 European registries were uploaded through the secure Virtual Private Network pipelines to the EuroSpA server, and pooled. Baseline characteristics were investigated with non-parametric descriptive statistics. TNFi retention rates (Kaplan-Meier statistics), and 28-joint count Disease activity Score (DAS28)<2.6 and 28 joint Disease activity index for Psoriatic arthritis (DAPSA28)≤4 were calculated, including LUNDEX adjustment 2 . For patients initiating 1 st TNFi after January 1 st 2009, the following sub-cohorts were also studied: patients known to be fulfilling ClASsification for Psoriatic aRthritis (CASPAR) criteria and patients with one or more swollen joints (swollen joint count (SJC)≥1) at baseline. Results: Overall, 14, 261 patients with PsA initiated a 1 st TNFi. Baseline characteristics of the pooled population are shown in the Table . The median 12-month retention rate (95%CI) was 77% (76-78%), ranging from 68-90% across registries (Figure ). Overall, DAS28/DAPSA28 remission rates at 6 months were 56%/27% (LUNDEX-adjusted: 45%/22%). In patients initiating a 1 st TNFi after 2009 with registered fulfillment of CASPAR criteria (n=1, 980) or registered ≥1 swollen joint at baseline (n=5, 803), the retention rates and remission rates were similar to those found overall (Table ). Conclusion: Approximately half of >14, 000 patients with PsA who initiated 1 st TNFi treatment in routine care were in DAS28-remission after 6 months, and three out of four were still on the drug after 1 year. References: [1] Clin Exp Rheumatol, 2018, 36(6):1068-1073 [2] arthritis Rheum, 2006, 54(2): 600-6 Acknowledgement: Novartis Pharma aG and IQVIA for supporting the EuroSpA collaboration. Disclosure of interests: Cecilie Heegaard Brahe Grant/research support from: Unrestricted grant: Novartis, Lykke Ørnbjerg Grant/research support from: Unrestricted grant: Novartis, Lennart T.H. Jacobsson Consultant for: LJ has received lecture and consulting fees from Pfizer, abbvie, Novartis, Eli-Lily and Janssen, Michael Nissen Consultant for: abbVie, Lilly, Novartis, and Pfizer, Eirik kristianslund: None declared, Heřman Mann Consultant for: Pfizer, Eli Lilly, Sanofi, Speakers bureau: abbVie, Roche, Pfizer, MSD, Eli Lilly, Sanofi, Maria Jose Santos: None declared, Manuel Pombo-Suarez: None declared, Dan Nordström Grant/research support from: MSD, Pfizer, Consultant for: abbVie, BMS, MSD, Novartis, Roche, Pfizer, UCB, Speakers bureau: Novartis, UCB, Ziga Rotar: None declared, Björn Gudbjornsson: None declared, Fatos onen: None declared, Catalin Codreanu: None declared, Ulf Lindström: None declared, Burkhard Moeller Consultant for: Swissmedic Human Medicines Expert Committee Member (regulatory agency), Joe Sexton: None declared, Karel Pavelka: None declared, anabela Barcelos: None declared, Carlos Sánchez-Piedra: None declared, Kari Eklund: None declared, Matija Tomsic: None declared, Thorvardur Jon Love Consultant for: Received reimbursment from Celgene for speaking about guidelines for the treatment of psoriatic arthritis, Gerçek Can: None declared, Ruxandra Ionescu: None declared, anne Gitte Loft: None declared, Marleen van de Sande Grant/research support from: van Janssen, Novartis, Eli Lily, Consultant for: Novartis and abbvie, Irene van der Horst-Bruinsma Grant/research support from: MSD, Pfizer, abbVie, Consultant for: abbvie, UCB, MSD, Novartis, Speakers bureau: BMS, abbVie, Pfizer, MSD, Gary Macfarlane Grant/research support from: Have received research grants (not current) from abbvie and Pfizer. Have received research grants (not current) from the British Society for Rheumatology, who received the funds from abbive, Pfizer and UCB. Have received research grant (current) from the British Society for Rheumatology, who received the funds from Celgene., Florenzo Iannone Consultant for: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, abbVie, MSD, BMS, Novartis, Lilly, UCB outside this work, Speakers bureau: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, abbVie, MSD, BMS, Novartis, Lilly, UCB outside this work, Lise Hyldstrup: None declared, Niels Steen Krogh: None declared, Mikkel Ǿstergaard Grant/research support from: abbvie, Celgene, Centocor, Merck, Novartis, Consultant for: abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Speakers bureau: abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Merete L. Hetland Grant/research support from: BMS, MSD, abbVie, Roche, Novartis, Biogen, Pfizer, Consultant for: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck, Samsung Bioepis